Evaluation of Project P.A.T.H.S. (Secondary 1 Program) by the Program Implementers: Findings Based on the Full Implementation Phase - Daniel T. L. Shek; Hing Keung Ma (The Scientific World Journal)
A total of 207 schools (N = 35,735 students) participated in the Secondary 1 Program of Project P.A.T.H.S. in the full implementation phase (2006/07 school year). After completion of the Tier 1 Program, 1,250 instructors completed a subjective outcome evaluation form (Form B) to assess their views of the program, instructors, and perceived effectiveness of the program. Utilizing the consolidated reports submitted to the funding body, the research team aggregated the consolidated data to form an overall profile of the perceptions of the program participants. Results showed that high proportions of the respondents had positive perceptions of the program and the instructors, and roughly four-fifths of the respondents regarded the program as helpful to the program participants and the workers. These findings complement the subjective outcome evaluation findings based on the perspective of the program participants.